2011
DOI: 10.1038/hr.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms in weight loss-induced blood pressure reduction between a calorie-restricted diet and exercise

Abstract: The present study compared the effectiveness of a mild calorie-restricted diet (D) alone, exercise (EX) alone and a combination of D+EX on weight loss-induced blood pressure (BP) reduction over 24 weeks. We focussed especially on the relationship between sympathetic nervous activity, as indicated from measures of plasma norepinephrine (NE), and insulin resistance (homeostasis model of insulin resistance, HOMA-IR). The three groups each comprised 30 obese, hypertensive men. Body mass index (BMI), fat mass, wais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…Obesity, hypertension and type 2 diabetes are characterized as stimulated sympathetic nervous activity and insulin resistance states, indicating renal injury and ESRD are strongly related to sympathetic nervous activity and insulin resistance. Masuo et al reported that significant weight loss resulted in significant amelioration on renal function following suppression on sympathetic activation and hyperinsulinemia (insulin resistance) [Masuo, et al 2012]. The findings suggest that strong linkage between sympathetic nervous activity, insulin resistance and renal function.…”
Section: Sympathetic Nervous Activity As a Risk Factor For Cardiovascmentioning
confidence: 84%
See 2 more Smart Citations
“…Obesity, hypertension and type 2 diabetes are characterized as stimulated sympathetic nervous activity and insulin resistance states, indicating renal injury and ESRD are strongly related to sympathetic nervous activity and insulin resistance. Masuo et al reported that significant weight loss resulted in significant amelioration on renal function following suppression on sympathetic activation and hyperinsulinemia (insulin resistance) [Masuo, et al 2012]. The findings suggest that strong linkage between sympathetic nervous activity, insulin resistance and renal function.…”
Section: Sympathetic Nervous Activity As a Risk Factor For Cardiovascmentioning
confidence: 84%
“…NE, plasma norepinephrine levels; Fat, total body fat-mass; SBP, systolic blood pressure; DBP, diastolic blood pressure; HOMA, homeostasis model of assessment of insulin resistance. [Masuo, et al 2012] Figure 2. When significant changes were observed comparisons between a calorie restricted diet vs. mild exercise alone vs. combination with diet + exercise over 24 weeks Very recently, Masuo et al [Masuo, et al 2012} showed the differences in mechanisms of weight loss-induced blood pressure reductions with neurohormonal parameters changes over 24 weeks with loss regimens (Figure 2).…”
Section: Relationships Between Sympathetic Nervous Activity and Insulmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss treated with lifestyle modification including calorie restriction and/or exercise causes normalization of stimulated RAAS, sympathetic activation, insulin resistance, and hyperleptinemia, which are usually observed in type 2 diabetes and obesity. Recently, Straznicky et al [4] and Masuo et al [5] have shown the low caloric diet and exercise have different effects on insulin resistance, the RAAS, and sympathetic nervous activity in obese hypertensive subjects, although similar weight loss was observed between both interventions. Straznicky et al [4] reported that exercise had stronger effects of normalized the RAAS stimulation, sympathetic activation and insulin resistance compared to diet only, whereas Masuo et al [5] showed mild calorie restriction and mild exercise has different mechanisms on weight loss (normalization on sympathetic activation for mild calorie restriction, and normalization on insulin resistance for exercise).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Straznicky et al [4] and Masuo et al [5] have shown the low caloric diet and exercise have different effects on insulin resistance, the RAAS, and sympathetic nervous activity in obese hypertensive subjects, although similar weight loss was observed between both interventions. Straznicky et al [4] reported that exercise had stronger effects of normalized the RAAS stimulation, sympathetic activation and insulin resistance compared to diet only, whereas Masuo et al [5] showed mild calorie restriction and mild exercise has different mechanisms on weight loss (normalization on sympathetic activation for mild calorie restriction, and normalization on insulin resistance for exercise). The observations, however, demonstrate that a combination therapy for weight loss with a low caloric diet and exercise is recommended for weight loss due to stronger suppression of insulin resistance and sympathetic activation, which both are known as strong risk factors for cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%